Steering by their own lights: Why regulators across Europe use different indicators to measure healthcare quality. Issue 5 (May 2020) - Beaussier, Anne-Laure; Demeritt, David; Griffiths, Alex; Rothstein, Henry
Highlights: Indicator sets differ in how they define, measure, and assess healthcare quality. National sets shaped by varying governance traditions and healthcare system configuration. Targeting of quality dimensions and hospital activities shaped by system-specific 'demand-side' pressures. Measurement styles shaped by 'supply-side' constraints on data access and indicator construction. International benchmarking is easier when healthcare systems and governance traditions are similar. Abstract: Despite widespread faith that quality indicators are key to healthcare improvement and regulation, surprisingly little is known about what is actually measured in different countries, nor how, nor why. To address that gap, this article compares the official indicator sets--comprising some 1100 quality measures-- used by statutory hospital regulators in England, Germany, France, and the Netherlands. The findings demonstrate that those countries' regulators strike very different balances in: the dimensions of quality they assess (e.g. between safety, effectiveness, and patient-centredness); the hospital activities they target (e.g. between clinical and non-clinical activities and management); and the 'Donabedian' measurement style of their indicators (between structure, process and outcome indicators). We argue that these contrasts reflect: i) how the distinctive problems facing each country's healthcare system create different 'demand-side' pressures on what national indicator sets measure; and ii) how the configuration of national healthcare systems and governance traditions create 'supply-side' constraints on the kinds of data that regulators can use for indicator construction. Our analysis suggests fundamental differences in the meaning of quality and its measurement across countries that are likely to impede international efforts to benchmark quality and identify best practice.